I-FiBH trial: intravenous fluids in benign headaches—a randomised, single-blinded clinical trial. Issue 8 (3rd July 2020) - Zitek, Tony; Sigal, Tiffany; Sun, Gina; Martin Manuel, Chris; Tran, Khanhha
Abstract : Background: Many emergency physicians use an intravenous fluid bolus as part of a 'cocktail' of therapies for patients with headache, but it is unclear if this is beneficial. The objective of this study was to determine if an intravenous fluid bolus helps reduce pain or improve other outcomes in patients who present to the ED with a benign headache. Methods: This was a randomised, single-blinded, clinical trial performed on patients aged 10–65 years old with benign headaches who presented to a single ED in Las Vegas, Nevada, from May 2017 to February 2019. All patients received prochlorperazine and diphenhydramine, and they were randomised to also receive either 20 mL/kg up to 1000 mL of normal saline (the fluid bolus group) or 5 mL of normal saline (the control group). The primary outcome was the difference between groups in mean pain reduction 60 min after the initiation of treatment. Secondarily, we compared groups with regards to pain reduction at 30 min, nausea scores, the use of rescue medications and disposition. Results: We screened 67 patients for enrolment, and 58 consented. Of those, 35 were randomised to the fluid bolus group and 23 to the control group. The mean pain score dropped by 48.3 mm over 60 min in the fluid bolus group, compared with 48.7 mm in the control group. The between groups difference of 0.4 mm (95% CI −16.5 to 17.3) was not statistically significant (p=0.96). Additionally, no statistically significant difference was found between groups for any secondary outcome. Conclusion: Though our study lacked statistical power to detect small but clinically significant differences, ED patients who received an intravenous fluid bolus for their headache had similar improvements in pain and other outcomes compared with those who did not. Trial registration number: NCT03185130 .